Connecting Theory and Practice in Teacher Education: Issues and Challenges - Adhikari, Yadav Raj (Prithvi Journal of Research and Innovation, 2022)
The study aims to explore the course teachers’ perceptions towards teaching practice. To meet the research objectives, interpretive paradigm was used adopting phenomenological research design based on qualitative research. The course teachers of teaching practice (Course No. Ed. 440) were its informants. They were selected purposively from Prithvi Narayan Campus, Pokhara, which is the largest constituent campus of Tribhuvan University. In-depth interviews were taken with six course teachers from different subjects to generate information. Though teaching practice is the core of teacher education program, it has some constrains. The course is designed to provide the hands-on experience to the prospective teachers through rigorous practice under the close supervision of course teachers, but the output is not found as expected and the program is also not free from criticism. The study revealed that the program was not achieving its objectives prescribed by the curriculum. It was just becoming teaching not training in reality. Lack of motivation and dedication of prospective teachers; similarly, devotion and integrity of supervisors, cooperation of cooperating schools, university’s policies, job opportunities in home country, unfair and flexible evaluation practices were explored as the main issues and challenges for its effective implementation and output. The findings of the study will be useful to the policymakers, professionals, prospective teachers and other stakeholders to reform the present phenomenon.